The Barrier Zones in the Ocean - Emelyanov, Emelyan M. (Springer Berlin Heidelberg : Imprint: Springer, 2005)
Geochemical barrier zones play an important role in determining various physical systems and characteristics of the oceans, e.g. hydrodynamics, salinity, temperature and light. In this book, each of the 40 barrier zones covered are illustrated and defined by physical-chemical parameters. Among the topics discussed are the processes of inflow, transformation and precipitation of the sedimentary layer of the open oceans and more restricted areas such as the Baltic, Black and Mediterranean Seas. This well-illustrated book may serve as the basis for courses such as "Marine Geochemistry" or "Ocean Usage" and can be useful to researchers in the fields of geology, geography, marine chemistry, geoecology and hydrochemistry.